Preventing HIV/AIDS in the Middle East and North Africa : a window of opportunity to act. - Akala, Francisca Ayodeji, 1968-; Jenkins, Carolyn M. (Carolyn Marion) (Orientations in development., 2005)
The HIV/AIDS epidemic has the potential to impede and even reverse development if not addressed early enough. Poverty and income inequality have been shown to facilitate the diffusion of HIV epidemics. While abject poverty in the Middle East and North Africa region remains low, a significant proportion of the population (23.2%) live under 2 per day and are extremely vulnerable in their ability to cope with shocks. In order to preserve the benefits of national and regional development investments put in place by governments, and donor agencies, greater investments to improve HIV/AIDS advocacy, i.